Architectural anatomy of the quadriceps and the relationship with muscle strength: An observational study utilising real‐time ultrasound in healthy adults. Issue 4 (29th August 2021) - El‐Ansary, Doa; Marshall, Charlotte J.; Farragher, Joshua; Annoni, Raquel; Schwank, Ariane; McFarlane, James; Bryant, Adam; Han, Jia; Webster, Marilyn; Zito, Guy; Parry, Selina; Pranata, Adrian
Abstract: Quadriceps atrophy and morphological change is a known phenomenon that can impact significantly on strength and functional performance in patients with acute or chronic presentations conditions. Real‐time ultrasound (RTUS) imaging is a noninvasive valid and reliable method of quantifying quadriceps muscle anatomy and architecture. To date, there is a paucity of normative data on the architectural properties of superficial and deep components of the quadriceps muscle group to inform assessment and evaluation of intervention programs. The aims of this study were to (1) quantify the anatomical architectural properties of the quadriceps muscle group (rectus femoris, vastus intermedius, and vastus lateralis) using RTUS in healthy older adults and (2) to determine the relationship between RTUS muscle parameters and measures of quadriceps muscle strength. Thirty middle aged to older males and females (age range 55–79 years; mean age =59.9 ± 7.08 years) were recruited. Quadriceps muscle thickness, cross‐sectional area, pennation angle, and echogenicity were measured using RTUS. Quadriceps strength was measured using hand‐held dynamometry. For the RTUS‐derived quadriceps morphological data, rectus femoris mean results; circumference 9.3 cm; CSA 4.6 cm 2 ; thickness 1.5 cm; echogenicity 100.2 pixels. Vastus intermedius mean results; thickness 1.8 cm; echogenicity 99.1 pixels. Vastus lateralis thickness 1.9 cm; pennation angle 17.3° ; fascicle length 7.0 cm. Quadriceps force was significantly correlated only with rectus femoris circumference ( r = 0.48, p = 0.007), RF echogenicity ( r = 0.38, p = 0.037), VI echogenicity ( r = 0.43, p = 0.018), and VL fascicle length ( r = 0.43, p = 0.019). Quadriceps force was best predicted by a three‐variable model (adjusted R 2 = 0.46, p < 0.001) which included rectus femoris echogenicity ( B = 0.43, p = 0.005), vastus lateralis fascicle length ( B = 0.33, p = 0.025) and rectus femoris circumference (B = 0.31, p = 0.041). Thus respectively, rectus femoris echogenicity explains 43%, vastus lateralis fascicle length explains 33% and rectus femoris circumference explains 31% of the variance of quadriceps force. The study findings suggest that RTUS measures were reliable and further research is warranted to establish whether these could be used as surrogate measures for quadriceps strength in adults to inform exercise and rehabilitation programs. Abstract : RTUS‐derived muscle architecture and morphology parameters may predict the variances of quadriceps strength in healthy adults. The study findings suggest that RTUS measures could be used to support quadriceps strength assessment in healthy adults where volitional assessment is impeded.